2019
DOI: 10.1007/s00359-018-01310-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autonomic denervations on the rhythms in axial length and choroidal thickness in chicks

Abstract: In chicks, axial length and choroidal thickness undergo circadian oscillations. The choroid is innervated by both branches of the autonomic nervous system, but their contribution(s) to these rhythms is unknown. We used two combination lesions to test this. For parasympathectomy, nerve VII was sectioned presynaptic to the pterygopalatine ganglia, and the ciliary post-ganglionics were cut (double lesion; n=8). Triple lesions excised the sympathetic superior cervical ganglion as well (n=8). Sham surgery controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In addition, Schmid et al reported that sympathectomy had an effect on ocular dimensions, and parasympathectomy could significantly influence AL, CT, and choroidal day-night fluctuation rhythm [ 49 ]. After parasympathectomy, AL and the fluctuation of CT increase, indicating that the parasympathetic nervous system influences CT and participates in the neural control mechanism of axial elongation [ 25 , 49 ]. Previous studies also indicate that the autonomic nervous system may play an important role in the development of myopia [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Schmid et al reported that sympathectomy had an effect on ocular dimensions, and parasympathectomy could significantly influence AL, CT, and choroidal day-night fluctuation rhythm [ 49 ]. After parasympathectomy, AL and the fluctuation of CT increase, indicating that the parasympathetic nervous system influences CT and participates in the neural control mechanism of axial elongation [ 25 , 49 ]. Previous studies also indicate that the autonomic nervous system may play an important role in the development of myopia [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, no effective treatment has been established to control axial elongation or prevent the progression of myopia. Previous studies have reported that the autonomic nervous system innervates the iris, ciliary muscle, and choroid of the eye, and regulates accommodation, choroidal thickness (CT), choroidal rhythm, and pupillary responses, which are closely related to the development of myopia [23][24][25][26]. By regulating the choroid and sclera, the autonomic nervous system plays an important role in the development of myopia [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%